Biodiesel synthesis via heterogeneous carbon acid catalysis from de-oiled jatropha curcas waste / Haziratul Mardhiah Hamdan - Haziratul Mardhiah, Hamdan (2017)
In the development of a more efficient and sustainable biodiesel production process, a heterogeneous carbon-based acid catalyst was prepared from the waste seed cake of Jatropha curcas (JC) left after de-oiling of the seeds to obtain the crude oil. The deoiled seed cake was carbonized into carbon form before sulfonated using sulfuric acid (H2SO4) to produce the catalyst. The physical and chemical properties of both the carbon precursor and the prepared carbon-based acid catalyst were characterized by a variety of techniques. The catalyst was consequently used to esterify the crude JC oil in order to lower the high free fatty acid content to acceptable levels (<4 mg KOH/g) before conversion into biodiesel can take place. The optimal esterification parameters of 12:1 methanol/oil ratio, 7.5 wt% catalyst, 60 °C, 60 min reaction time at 360 rpm were determined to effectively achieve a maximum conversion yield of 99.13%. The catalytic activity of the catalyst reduced gradually when re-used during multiple esterification cycles but maintained good stability in catalytic activity up to the 4th cycle. The esterified oil was converted into biodiesel by base-catalyzed transesterification under parameters of 1 wt% potassium hydroxide, 6:1 methanol/oil ratio, 60 °C for 60 minutes. The process produced 96% biodiesel yield that met the ASTM D6751 and EN14214 standards. Changes occurred to the properties of the crude JC oil, esterified oil and biodiesel were determined to have improved significantly after utilizing the catalyst in the biodiesel production process. Overall, the prepared carbon-based acid catalyst proved to be an effective and a more sustainable catalyst option to be utilized in the esterification process of JC oil, in producing high yield and quality biodiesel. Keyword: Carbon-based acid catalyst, Jatropha curcas, Seed cake, Parameter, Biodiesel